Theoretical study of atomic level understanding of the reactive ion etching (RIE) - Muhida, Rifki; Rahman, Md. Mamudur; Chowdhury, Md. Sazzad Hossien; Muhida, Riza; Zainuddin, Hishamuddin; Zakaria, Azmi; Kasai, Hideaki (American Scientific Publishers, 2012)
We consider cluster model of FeNi4 cluster (as material target) where Fe ion is surrounded by four Ni ions in order to understand the mechanisms involved in the reactive ion etching (RIE) processes on magnetic surfaces(e.g., FeNi surface). By considering CO ions as reactive gases, we etch Fe ion from the cluster surface providing ion pentacarbonyl, i.e., Fe(CO)5. By density functional theory based first principle calculations, we calculate the potential energy surface(PES) of the system and describe the mechanism of the reaction. Based on the two chosen pathways for initial and final states, we show that the RIE processes follow the pathway that gives us minimum energy.